Incidencia del tostado del grano de soya nacional (Glycine max) en la elaboración de balanceados en la planta PRONACA - Quevedo - Yaguana Sarango, Juan Vicente (2012)
The present investigation is carried out it in the Plant of having Balanced Pronaca-Quevedo located in the Km 29 of the road Quevedo – Sto Domingo, County of Los Ríos whose geographical situation is 79 º 18’ longitudes this. 00º 54´ south latitude. Altitude 260 m.s.n.m. with a precipitation average annual de1867 mm and an annual half temperature of 25ºC. The duration of the experiment was of seven months from Julio to January. The main objective of the following investigation was to determine the good levels of humidity for the one toasted of soya using two times of having toasted in the band transportadora with different grades of temperature in the camera of having toasted. A design experimental trifactorial 2*3*2 first floor a totally random design is applied, the treatments combined in the following way: T1 soya with 11% of humidity with 29.5 rpm in the band transportadora and 610 - 650 ºF in the camera of having toasted. T2 soya with 11% of humidity with 29.5 rpm in the band transportadora and 651 - 690 ºF in the camera of having toasted. T3 soya with 11% of humidity with 30.5 rpm in the band transportadora and 610 - 650 ºF in the camera of having toasted. T4 soya with 11% of humidity with 30.5 rpm in the band transportadora and 651 - 690 ºF in the camera of having toasted. T5 soya with 11% of humidity with 31.5 rpm in the band transportadora and 610 - 650 ºF in the camera of having toasted. T6 soya with 11% of humidity with 31.5 rpm in the band transportadora and 651 - 690 ºF in the camera of having toasted. T7 soya with 12% of humidity with 29.5 rpm in the band transportadora and 610 - 650 ºF in the camera of having toasted. T8 soya with 12% of humidity with 29.5 rpm in the band transportadora and 651 - 690 ºF in the camera of having toasted. T9 soya with 12% of humidity with 30.5 rpm in the band transportadora and 610 - 650 ºF in the camera of having toasted. T10 soya with 12% of humidity with 30.5 rpm in the band transportadora and 651 - 690 ºF in the camera of having toasted. T11 soya with 12% of humidity with 31.5 rpm in the band transportadora and 610 - 650 ºF in the camera of having toasted. T12 soya with 12% of humidity with 31.5 rpm in the band transportadora and 651 - 690 ºF in the camera of having toasted. For the execution of the investigation you proceeded firstly to the reception of the matter it prevails and mensuration of the humidity, then a pre cleaning, then a drying until obtaining a soya of 12% and 11% of humidity, later on sifts it to him and he/she passes to toast, and finally it stores it to him in a silo. The experimental mensurations of the product finished as the tripsina inhibitors are carried out them in the Laboratory nutrianalisis in Bogotá-Colombia and the protein analyses, activity ureasica and solubility in the Laboratory of the Plant Pronaca-Quevedo.